PENGGUNAAN MODEL PICTURE AND PICTURE UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN BAHASA INGGRIS KELAS IX SMP NEGERI 4 PONTIANAK - Fatimah, Fatimah (Jurnal Pembelajaran Prospektif, 2025)
This study aims to design a lesson plan by applying the Picture and Picture model to improve students"™ motivation and learning outcomes in English subjects; to implement learning using the Picture and Picture model to increase students"™ motivation in English subjects; and to improve students"™ learning outcomes in English through the use of the Picture and Picture model. The research was conducted in Class IX of SMP Negeri 4 Pontianak during the 2020/2022 academic year. This study employed a descriptive research method in the form of Classroom Action Research (CAR), using a spiral model of self-reflection starting from: planning, acting, observing, and reflecting, carried out over two cycles. The results showed that in the planning stage, using the Picture and Picture model in both Cycle 1 and Cycle 2, there was an increase in Cycle 2. In Cycle 1, the score percentage was 76.5%, which increased to 88% in Cycle 2. The implementation stage using the Picture and Picture model also showed improvement in Cycle 2, with a score percentage increasing from 72% in Cycle 1 to 83% in Cycle 2. Furthermore, the Picture and Picture model was effective in improving students"™ learning outcomes in terms of cognitive, affective, psychomotor, and motivational aspects. Therefore, it can be concluded that the use of the Picture and Picture model successfully enhanced students"™ learning outcomes and motivation